1970
DOI: 10.1111/j.1476-5381.1970.tb10373.x
|View full text |Cite
|
Sign up to set email alerts
|

Rapid method for the determination of 5‐hydroxytryptamine and 5‐hydroxyindoleacetic acid in small regions of rat brain

Abstract: A rapid and sensitive method for measuring 5‐hydroxytryptamine and 5‐hydroxyindoleacetic acid, using o‐phthalaldehyde and L‐cysteine, is presented, enabling both compounds to be measured in small areas of rat brain.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
186
0

Year Published

1975
1975
2002
2002

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 936 publications
(189 citation statements)
references
References 15 publications
2
186
0
Order By: Relevance
“…5-HT and phenylethylamine oxidation were only inhibited by more than 90% at the higher dose, whilst 5-HT concentrations only rose to about those observed after tranylcypromine (2.5 mg/kg) at the same dosage combination (Table 4). Squires (1975) suggested that hyperactivity is seen only when clorgyline and deprenil are given together because it stems from the action of a Table 3 Effect of various doses of clorgyline or deprenil with or without L-tryptophan injection (100 mg/kg) 30 min later on brain 5-hydroxytryptamine (5-HT) concentrations and monoamine oxidase (MAO) activity towards 5-HT, dopamine and phenylethylamine 120 min after initial injection (Curzon & Green, 1970) and that of Squires & Buus Lassen (1975) is somewhat non-specific, for it will measure other 5-substituted indoles (Maickel & Miller, 1966). Since 5-methoxytryptamine is present in the hypothalamus (Green, Koslow & Costa, 1973), produces a strong fluorescent reading with OPT and gives rise to behavioural changes similar but not identical to those seen following increased 5-HT synthesis (Green, Hughes & Tordoff, 1975), it was important to ascertain that the apparent rise of 5-HT seen after tranylcypromine and tryptophan does not derive spuriously from this or another 5-substituted pharmacologically active indoleamine.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…5-HT and phenylethylamine oxidation were only inhibited by more than 90% at the higher dose, whilst 5-HT concentrations only rose to about those observed after tranylcypromine (2.5 mg/kg) at the same dosage combination (Table 4). Squires (1975) suggested that hyperactivity is seen only when clorgyline and deprenil are given together because it stems from the action of a Table 3 Effect of various doses of clorgyline or deprenil with or without L-tryptophan injection (100 mg/kg) 30 min later on brain 5-hydroxytryptamine (5-HT) concentrations and monoamine oxidase (MAO) activity towards 5-HT, dopamine and phenylethylamine 120 min after initial injection (Curzon & Green, 1970) and that of Squires & Buus Lassen (1975) is somewhat non-specific, for it will measure other 5-substituted indoles (Maickel & Miller, 1966). Since 5-methoxytryptamine is present in the hypothalamus (Green, Koslow & Costa, 1973), produces a strong fluorescent reading with OPT and gives rise to behavioural changes similar but not identical to those seen following increased 5-HT synthesis (Green, Hughes & Tordoff, 1975), it was important to ascertain that the apparent rise of 5-HT seen after tranylcypromine and tryptophan does not derive spuriously from this or another 5-substituted pharmacologically active indoleamine.…”
Section: Resultsmentioning
confidence: 99%
“…Rats were injected with tranylcypromine (20 mg/kg) followed by L-tryptophan (100 mg/kg) 30 min later. After a further 60 min, the rats were killed, the brains divided down the mid-line and 5-HT measured in one half by the OPT method (Curzon & Green, 1970) and in the other by the ninhydrin method of Snyder, Axelrod & Zweig (1965) which at the appropriate wave length appears to measure only 5-HT (Snyder et al, 1965). As they were so similar, the results suggested that the OPT method was measuring only 5-HT (Table 5) and that no other 5-substituted indoles were present.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Brain 5-HT was measured in whole brain and spinal cord (from immediately behind the cerebellum to approximately T5) by the fluorometric method of Curzon & Green (1970).…”
Section: Biochemical Measurementsmentioning
confidence: 99%
“…Serotonin was estimated by the method of Curzon and Green [6], and catecholamines by the method of Well-Malherbe [23]. Quinolinic acid content of plasma was estimated by HPLC (C 18 column micro Bondapak 4.6 £ 150 mm), solvent system 0.01 M acetate bu er (pH 3.0) and methanol (6:4),¯ow rate 1.0 mL=min, and detection UV 250 nm).…”
Section: Methodsmentioning
confidence: 99%